Pengenalan Narkoba Pada Anak Usia Dini Melalui Pendekatan Metode Bercerita - Raihana, Raihana; Nurhayati, Siti; Muazimah, Ajriah (Generasi Emas, 2018)
Underage drug users show very large numbers, so understanding the dangers of drugs needs to be planted as early as possible. Supervision is not only done by parents at home, but also by teachers and the surrounding community. Through the method of telling children, it is expected to be able to distinguish good deeds and bad deeds so that they can be applied in daily life. The method of telling stories using illustrated storybooks that are packaged in an interesting way can be of particular concern to children. The adverse effects of drug use, for children not only will lose their future but will also lose their identity as young people who are creative and innovative, using drugs means children damage themselves, because as we all know that drug use will continually damage the nervous system the brain that will be felt throughout his life, even if the person has stopped using drugs. The method of telling stories by conveying information and knowledge to early childhood about the adverse effects of drug use is fun and will be stored in memory until adulthood so that the hopes and desires to make the younger generation will avoid drugs will be realized.